Peningkatan Keaktifan Siswa Melalui Penerapan Problem Based Learning (PBL) pada Materi "Aku Memiliki Kemampuan" di SMP Negeri 7 Sintang - Nikodimus Martin Kodinar; Timotuis Tote Jelahu; Modestus Haryono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Student engagement in learning plays a crucial role in enhancing material comprehension and learning motivation. Active students are more likely to engage in critical thinking, participate in discussions, and solve problems presented to them. However, in many schools, student engagement remains low due to passive teaching methods, such as lectures. To address this issue, the Problem Based Learning (PBL) method is implemented. PBL encourages students to actively solve real-world problems relevant to their lives, thereby increasing their involvement and participation in the learning process. This research aims to improve the engagement of grade VIII students at SMP Negeri 7 Sintang on the Aku Memiliki Kemampuan topic through the application of PBL. The results indicate that PBL successfully enhanced student engagement, with student participation increasing from 30% in the initial condition to 85% after two learning cycles. Additionally, the students' average scores significantly improved. Thus, PBL is proven effective in enhancing both student engagement and learning outcomes.